Researching the 1980s competitions in Kyiv – preconditions of the After Socialist Modernism (City: History, Culture, Society, 2022)
The 1980s recently became a contested period in the architectural and urban planning history of Eastern Europe and the FSU countries. Situated within the Socialist Modernism timeframe, it at the same time forms a link to the manifold political and economic change happening in 1989\1991. While professionals posed radical questions about the core issues of the Socialist socio-spatial development and acquired new sensibilities towards history and locality, their influence on decision-making often remained seriously restrained by the construction industry.In Kyiv as well as in most of the big cities of the USSR, however, a change in the approach towards areas in the city center was visible – competitions, discussions, and iterative design were becoming a new norm for the architects and planners. In this paper, three projects on the block scale are reviewed in detail. These chosen competition projects became the watershed between modernist and after-modernist approaches to planning, showcasing new contextualized spatial solutions. What standards had been formed and what were the long-term impacts on the planning processes are the issues given the first attempt to answer. The intention of this paper is to gain a better understanding of the recent past towards intensifying the discourse about the sources of the present of urban development in Kyiv and beyond.
Keywords: Postmodernism; Socialist Modernism; Kyiv; 1980s; Tafuri